Desafios dos acadêmicos indígenas Xerente permeados pela tecnologia em aldeias - Xerente, Elizabeth Kuzeidi de Brito (Universidade Federal do Tocantins, 2024)
This undergraduate thesis addresses how indigenous students from the Federal University of Tocantins (UFT), Miracema Campus, experienced university life during the Covid-19 pandemic. It aims to understand these students' life trajectories up to their admission to UFT, focusing on the pandemic context, particularly the obstacles encountered with the adoption of different technologies for accessing classes and other activities, considering social isolation. Through qualitative research, the reflection presented in this study was developed based on a bibliographic review, incorporating relevant research information. The results indicated that indigenous students faced significant challenges, such as inadequate access to the internet and technological devices, which hindered their effective participation in academic activities. Additionally, they revealed that the university was not prepared for the emergency scenario. Despite these challenges, students sought alternatives to continue their studies, such as using community spaces and sharing technological resources with peers. It is hoped that this study may contribute to future discussions on digital inclusion policies and student support, aiming for a more inclusive and equitable university for indigenous students.